Screening for antioxidant activity, phenolic content, and flavonoids from australian native food plants - Sarana Sommano (2018)
Seven kinds of bush plants, namely, bush tomato (BT), lemon myrtle (LM), wild lime (WL), finger lime (FL), wattle seed (WS), Davidson's plum (DP), and Kakadu plum (KP) were investigated for antioxidant capacity by 2,2-diphenyl-1-picrylhydrazyl radical, Trolox equivalent antioxidant capacity assay, or 2,2'-azinobis-93-ethyl-benzothiazoline-6-sulfonic acid radical, total polyphenols, and flavonoids. It was found that there was a positive correlation between antioxidant activities examined by the two methods. However, there was a negative correlation between total phenol and each of the antioxidant activity tests; for example, Davidson's plum contained the phenolic content as high as 890 mg GAE/100 g while low antioxidant activities were detected (23 TE/100 g and 45% for TEAC and % DPPH, respectively). For the qualitative flavonoids test, bush tomato contained feulic acid, caffeic acid, naringenin, and hesperetin. Lemon myrtle contained catechin, epicatechin, vanilic acid, myricetin, kampferol, and naringenin. Finger lime contained caffeic acid and vanilic acid. Wild lime contained epicatechin, vanilic acid, luteolin, and naringenin. Kakadupum contain catechin and naringenin. Davidson's plum contained naringenin and hesperetin. Wattle seed contained naringenin. However, some other compounds could not be identified because there was no standard to confirm the retention time available. Absorbance was changed for the detection of anthocyanins in Davidson's plums from 220-400 to 525 nm. It was shown by liquid chromatography mass spectrometry that six major anthocyanidins (delphinidin, cyanidin, petunidin, pelargonidin, peonidin, and malvidin) attached with the sugar molecules (hexose and pentose) were found and the major anthocyanin was cyaniding-hexose-pentose. This study suggests that regarding the antioxidant capacity, these Australian Native plants have potential as functional food ingredients. © 2013 Copyright Taylor & Francis Group, LLC.